Дискримінація за віком: правовий аспект - Грень , Наталія Михайлівна (Національний університет «Львівська політехніка», 2023)
Дисертація присвячена вирішенню науково-прикладної проблеми, що має важливе значення для правової науки та полягає у комплексному теоретико-правовому розумінні дискримінації за віком і формуванні належної правової політики протидії та запобігання віковій дискримінації. Мотивовано, що термінопоняття «дискримінація» не має усталеного юридичного розуміння, що зумовлено мультинауковістю поняття та повсякчасним оновленням тлумачення та розширенням ознак під впливом глобалізації правової реальності. Констатовано взаємодію понять «справедливість», «рівність» та «недискримінація», їх взаємозалежність. Однак покритиковано підхід, в якому вищезазначені категорії сприймаються як тотожні спираючись на наукові положення та тлумаченням рішень Конституційних судів Польщі, Латвії, Чехії, Верховного суду Німеччини та судових органів Франції. Автором виокремлено наступні особливості допустимості відхилення від ідеї рівності заради досягнення принципу недискримінації: обґрунтування відхилень від правила рівного ставлення мають бути актуальними; розумна пропорційність відхилення; законність; пропорційність відхилення не має суперечити основоположній ідеї права – забезпеченню справедливості. Визначено основні характеристики вікової дискримінації: дискримінаційною характеристикою є вік особи; на відміну від інших видів, характеризується тим, що потенційною жертвою може бути будь-яка особа; простежується змінність ознаки дискримінації протягом життя; має ширшу латентність, ніж інші її види та є найбільш соціально толерованою; вік є особливо складним для тлумачення ознаки як дискримінаційної. The dissertation is devoted to solving a scientific and applied problem of great importance for legal science, which is a comprehensive theoretical and legal understanding of age discrimination and the formation of an appropriate legal policy to combat and prevent age discrimination. The author argues that the term "discrimination" does not have a well-established legal understanding, which is due to the multidisciplinary nature of the concept and the constant updating of its interpretation and expansion of its features under the influence of globalization of legal reality. The author notes the interaction of the concepts of "justice", "equality" and "non-discrimination" and their interdependence. However, the author criticizes the approach in which the above-mentioned categories are perceived as identical based on scientific provisions and interpretations of decisions of the Constitutional Courts of Poland, Latvia, the Czech Republic, the Supreme Court of Germany and the judicial authorities of France. The author identifies the following features of the admissibility of deviations from the idea of equality in order to achieve the principle of non-discrimination: the justification for deviations from the rule of equal treatment must be relevant; reasonable proportionality of deviation; legality; the proportionality of deviation must not contradict the fundamental idea of law - ensuring justice. The author defines the main characteristics of age discrimination: the discriminatory characteristic is a person's age; unlike other types, it is characterized by the fact that any person can be a potential victim; the variability of the discrimination feature can be traced throughout life; it has a wider latency than other types of discrimination and is the most socially tolerated; age is particularly difficult to interpret as discriminatory.
Age discrimination: legal aspect
Keywords: дискримінація, ознаки дискримінації, вікова дискримінація, множинна дискримінації за віком, пряма дискримінація, непряма дискримінація, протидія дискримінації, запобігання дискримінації, гарантії протидії віковій дискримінації, діти, особи літнього віку, discrimination, signs of discrimination, age discrimination, multiple age discrimination, direct discrimination, indirect discrimination, combating discrimination, prevention of discrimination, guarantees of combating age discrimination, children, elderly persons.; 340.12:316.647.82](043.5)